Utilizing Design Thinking and User Experience Research for Effective Agricultural Labor Recruitment Web Application Design - Sabrina, Cut Luna; Astiti, Sarah (LPPM Institut Teknologi Telkom Purwokerto, 2024)
The agricultural sector faces a significant challenge in recruiting a skilled workforce, with both landowners and tenant farmers struggling to find new laborers. Factors such as inadequate rural infrastructure and facilities, coupled with limited technology adoption, have diminished the appeal of working in the agricultural sector. Consequently, agricultural productivity has declined due to a shortage of adequate labor. To address this issue, a prototype web application named “Partner Tani” was designed to facilitate labor recruitment for farmers. The application design process employed the Design Thinking methodology and the User Experience Questionnaire (UEQ) to thoroughly understand user requirements. The design outcomes encompass both user interface and administrator interface components, developed using Figma. The prototype application features functionalities such as login, account registration, profile management, job posting and search, and complaint reporting. Evaluation using the UEQ revealed that the prototype application achieved exceptional scores across all user experience dimensions: Attractiveness (average score: 2,11), Perspicuity (average score: 1,42), Efficiency (average score: 2,33), Dependability (average score: 1,50), Stimulation (average score: 1,75), and Novelty (average score: 1,67). Average scores for Attractiveness, Efficiency, Stimulation, and Novelty fell within the “Excellent” range, while Perspicuity and Dependability scores were above average. These findings indicate that the “Partner Tani” application prototype holds promise in delivering a satisfying and efficient user experience for agricultural labor recruitment.